Absence of mouse mammary tumor virus proviral amplification in chemically induced lymphomas of RF/J mice. - Kraft, R (1989)
RF/J mice are susceptible to the induction of thymic lymphomas by the carcinogens 3-methylcholanthrene and N-methyl-N-nitrosourea. Given the association of mouse mammary tumor virus (MMTV) with certain thymomas, we examined genomic DNA from chemically induced lymphomas of RF/J mice for new MMTV proviruses. Of 13 tissue culture lines derived from 3-methylcholanthrene-induced tumors, 5 had acquired new proviruses. MMTV amplification coincided with the appearance of viral mRNAs and proteins. However, no primary tumors or animal-passaged tumors contained new proviruses. These observations indicate that MMTV does not have a role in the tumor induction process, although it may become activated and amplified in tissue culture lines derived from tumors.